IOT office assistant system - See, King Li (2023)
This project is an IoT solution project which designed for academic purposes only. The methodology, concept, design skills for hardware and software will be provided through this project. This will be illustrated through the construction of an IoT office assistant system. Since the Raspberry Pi is suitable for the hardware implementation, therefore, it is implemented in the project. The Raspberry Pi is used as a CPU that can control and monitor the whole system. The tool used in this project is Eagle Software, it is used to design the layout of the PCB so that all the hardware components can be integrated on PCB. Besides, two Raspberry Pi is used in the project. One of the Raspberry Pi is used to collect data from the sensors while another Raspberry Pi is used for display information. The data such as the sensor’s reading value are stored using Firebase Real-Time Database for the system. Moreover, the system of this project can be divided into hardware and software part. The hardware part is included PCB design and uses Raspberry Pi integrated with components such as sensors and LCD while the software part is the system function design which uses Python programming language and Flutter for mobile application development. The mobile application is used for lecturer to configure the system and monitor the office. Finally, an IoT solution for the office assistant system is developed to help the lecturer in monitoring the office.